2017
DOI: 10.3389/fnagi.2017.00385
|View full text |Cite
|
Sign up to set email alerts
|

Linking Inter-Individual Variability in Functional Brain Connectivity to Cognitive Ability in Elderly Individuals

Abstract: Increasing evidence suggests that functional brain connectivity is an important determinant of cognitive aging. However, the fundamental concept of inter-individual variations in functional connectivity in older individuals is not yet completely understood. It is essential to evaluate the extent to which inter-individual variability in connectivity impacts cognitive performance at an older age. In the current study, we aimed to characterize individual variability of functional connectivity in the elderly and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 81 publications
(147 reference statements)
4
22
0
Order By: Relevance
“…However, among the associative regions, we found evidence of a medial–lateral dissociation; voxels in the medial prefrontal cortex and precuneus were highly likely to retain their network assignment across the six atlases, while the opposite was the case for voxels in the lateral frontal regions. These results are aligned with reviews (Eriksson, Vogel, Lansner, Bergstrom, & Nyberg, ; Nyberg & Eriksson, ) which have confirmed that the lateral aspects of the cortex show high interindividual variability, since these regions are crucial in implementing cognitive control (Moser et al, 2018; Niendam et al, ) and their variability is thought to underpin interindividual differences in executive functions (Gordon et al, ; Li et al, ; Mueller et al, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, among the associative regions, we found evidence of a medial–lateral dissociation; voxels in the medial prefrontal cortex and precuneus were highly likely to retain their network assignment across the six atlases, while the opposite was the case for voxels in the lateral frontal regions. These results are aligned with reviews (Eriksson, Vogel, Lansner, Bergstrom, & Nyberg, ; Nyberg & Eriksson, ) which have confirmed that the lateral aspects of the cortex show high interindividual variability, since these regions are crucial in implementing cognitive control (Moser et al, 2018; Niendam et al, ) and their variability is thought to underpin interindividual differences in executive functions (Gordon et al, ; Li et al, ; Mueller et al, ).…”
Section: Discussionsupporting
confidence: 84%
“…The SMN and VIS showed the highest similarity between the six different atlases. This was not surprising as these networks are comprising mostly of sensory and motor regions, which are known to have low interindividual variability in anatomical morphology (White et al, ) and in resting‐state FC (Franco et al, ; Li et al, ; Mueller et al, ) and tend to preferentially participate in single networks (Yeo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Across the three late-life cohorts, we found that the most reproducible networks were the SMN and VIS networks. These networks are mostly covering primary cortices, which are known to have high structural-functional coherence (Luo et al, 2020a), low inter-individual variability in anatomical morphology (White et al, 1997) and in resting-state functional connectivity (Franco et al, 2013;Li et al, 2017;Mueller et al, 2013), and tend to preferentially participate in single networks in line with their circumscribed and specific functions (Yeo et al, 2014). In contrast, the SAL network showed the largest spatial differences across the three late-life cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding normal inter-subject variance can help understand differences in cognitive outcomes between patients and optimize the full potential of neuroimaging applications. Moreover, inter-subject variance may be related to behavioral functions (75,76) and could provide useful clinical information with regards to predicting outcome in a patient population. Whereas, group studies examine mean effects across subjects, inter-subject variance may provide critical information, and should not be ignored.…”
Section: Single-subject Level Vs Group-level Analysesmentioning
confidence: 99%